A A Survey Of Reading Habits Of Pre-Service English Teachers In The School Of Teacher Training And Education - Astuti, Sari; sudirman (JOLADU: Journal of Language Education, 2024)
This study explores the reading habits of pre-service English teachers enrolled in a School of Teacher Training and Education. Utilizing a mixed-methods approach, the research aims to identify the frequency, preferences, and motivations behind the reading activities of these future educators. Data was collected through questionnaires distributed to 54 respondents and semi-structured interviews, providing both quantitative and qualitative insights. The findings indicate The questionnaires were distributed to 54 pre-service English teachers. The statistical analysis of the data indicates that even if the majority of students have read English since they were young, they may not necessarily have good reading habits in English, specifically. It appears that just a tiny portion of them have consistent reading habits in English based on their eagerness to regularly spend time reading various types of English texts. The study also shows that most of students prefer reading fiction texts instead of academic texts which reveals the imbalanced approach toward their reading habits. Factors influencing these habits include academic demands, personal interests, and the increasing accessibility of digital content. The study underscores the importance of fostering robust reading habits among pre-service teachers to enhance their professional development and effectiveness in the classroom. The implications of these findings suggest the need for targeted interventions and support mechanisms within teacher training programs to promote a balanced and enriching reading culture.